2021
DOI: 10.1002/jcla.23741
|View full text |Cite
|
Sign up to set email alerts
|

The gene expression of long non‐coding RNAs (lncRNAs): MEG3 and H19 in adipose tissues from obese women and its association with insulin resistance and obesity indices

Abstract: Background There is evidence regarding the role of two lncRNAs: MEG3 and H19 the pathomechanism of obesity and related disorders. Here, we aimed to evaluate the expression of MEG3 and H19 in visceral adipose tissues (VAT) and subcutaneous adipose tissues (SAT) of obese women (n = 18), as compared to normal‐weight women (n = 17). Moreover, we sought to identify the association of expression of MEG3 and H19 in SAT and VAT with obesity parameters, insulin resistance, and the mRNA expression of possible target gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…A case-control study demonstrated that lower lncRNA H19 expression, and increased miRNA-29b, a miRNA-29b expression associated with the severity of T2DM patients [17]. Moreover, an inverse correlation between the transcript level of H19 and obesity indices, HOMA-IR values and SAT expression was found in humans [18].…”
Section: The Functions Of H19 In Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study demonstrated that lower lncRNA H19 expression, and increased miRNA-29b, a miRNA-29b expression associated with the severity of T2DM patients [17]. Moreover, an inverse correlation between the transcript level of H19 and obesity indices, HOMA-IR values and SAT expression was found in humans [18].…”
Section: The Functions Of H19 In Glucose Metabolismmentioning
confidence: 99%
“…Glucose metabolism Hippocampal neuron apoptosis and [25] Wnt3, β-catenin, TCF-1, Bax, caspase-8, caspase-3, GSK-3β, Bel-2, Wnt signaling [28] CNS complications Glucose homeostasis and β cell function [9,[13][14] MiR-let 7, PI3K/AKT [9] H19/miR-1 40/HE4 [17] Fox O1 [18] Hnf4a [21] Diabetic cardiomyopathy Oxidative stress, inflammation, apoptosis, and autophagy [32][33] H 19/microRNA-675 axis, VDAC 1 [33,[36][37] Diabetic retinopathy Endothelial-mesenchymal transition [40] NOX4 and eNOS/NO signalings [43] Diabetic nephropathy Vitamin D receptor, miR-675 [45] EGR1 [45] Diabetic enteropathy IECs [49] MiR-141-3p, β-catenin [49] Diabetic wounds Angiogenesis [51] H 19/let-7, insulin-PI3 KA-kt pathway [9] Proliferation activity of keloid fibroblasts [53] Lymphatic endothelial cells [60] EZH2-mediated histone methylation, HIF-1a signal pathway [61] Gestational diabetes Igf2 and H 19 gene expression [13] Methylation of the H 19-Igf2 ICR [72] CNS: Central nervous system; ICR: Imprinting control region; IECs: Intestinal epithelial cells; EGR1: Early growth response protein 1.…”
Section: Dm and Complications Functions [Ref]mentioning
confidence: 99%
“…Additionally, the expression levels of both ACC1 and FAS, two critical molecules required for fatty acid biogenesis, were elevated in obese patients. In addition, the expression of H19 was negatively correlated with FAS, suggesting the essential participation of H19 in fatty acid biogenesis [ 66 ]. On the other hand, recent studies have investigated H19 in non-invasive samples, such as blood plasma and serum.…”
Section: Lncrnas In Insulin Resistancementioning
confidence: 99%
“…Furthermore, in a study carried out in samples of SAT and VAT adipose tissue from women, MEG3 expression in SAT had a significant relationship with obesity indices. In addition, MEG3 expression in SAT was positively correlated with PPARγ and FAS expression ( Figure 3 ), suggesting an essential role for MEG3 in obesity-related conditions [ 66 ]. Cheng et al identified an increase in the expression of MEG3 in endothelial cells isolated from white adipose tissue compared to those from the skeletal muscle or liver of obese mice.…”
Section: Lncrnas In Insulin Resistancementioning
confidence: 99%
“…Specific regulations of metabolically sensitive lncRNAs in mice have been demonstrated [10]. On the other hand, the association between the expression pattern of MEG3, H19, and obesity parameters, essential genes in adipose tissues from obese women have been reported [5].…”
Section: Introductıonmentioning
confidence: 99%